Teatro - Educação e ludicidade: novas perspectivas em educação - Santiago da Costa, Alexandre (Revista Entreideias: educação, cultura e sociedade, 2007)
O presente trabalho tem como objetivo desenvolver algumas reflexões acerca dos novos paradigmas didáticos que aportam como alternativas para superar as dificuldades apresentadas pelos educadores perante o trabalho pedagógico. A metodologia configurou-se como uma pesquisa bibliográfica acerca dos principais autores que atualmente referenciam educadores e pesquisadores da área da Arte-Educação,Teatro-Educação e da ludicidade. O trabalho com o Teatro-Educação configura-se a partir de pressupostos da ludicidade, como plenitude do educando, consciência dos docentes no trabalho a ser desenvolvido, corporeidade privilegiada e contextualização social. Aportamos, então, com uma abordagem didática que preconiza a educação de uma forma crítica, mas também priorizando os aspectos da emoção, da sensibilidade, do corpo e da consciência no trabalho pedagógico. Palavras-chave: teatro-educação; educação e ludicidade. Abstract: The present work aims to develop some reflexions about the nem didactic paradigms that appear an alternative to overcome the difficulties brought by the teachers educations towards the pedagigic work. The methodology was configurated as a bibliographic research about the main authors that are nowadays a reference to educators and researchers in the art-education, play way and playfulness area. The work with art-education is shaped from the pressupositions of the playfulness theory, such as: the plenitude of the student, the awareness of the teachers on the work snat is about to be developed, privileged body awareness and social contextualitation. we base on an educational approach that extols a critical form of education, but algo gives priority to the aspects of emotio, sensitivity, the body and the awareness on the pedagogic work.Abstract: The present work aims to develop some reflexions about the nem didactic paradigms that appear an alternative to overcome the difficulties brought by the teachers educations towards the pedagigic work. The methodology was configurated as a bibliographic research about the main authors that are nowadays a reference to educators and researchers in the art-education, play way and playfulness area. The work with art-education is shaped from the pressupositions of the playfulness theory, such as: the plenitude of the student, the awareness of the teachers on the work snat is about to be developed, privileged body awareness and social contextualitation . we base on an educational approach that extols a critical form of education, but algo gives priority to the aspects of emotio, sensitivity, the body and the awareness on the pedagogic work. Key words: play way, wducation and playfulness key-words: play way, wducation and playfulness.